Conjuring up Prehistory Landscape and the Archaic in Japanese Nationalism - Hudson, Mark J. (Archaeopress, 2021)
This study considers the ways in which archaeology and landscapes of the archaic have been appropriated in Japanese nationalism since the early twentieth century, focusing on the writings of cultural historian Tetsurō Watsuji, philosopher Takeshi Umehara and environmental archaeologist Yoshinori Yasuda
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1920-; Archaeology--Japan; Landscape archaeology--Japan; Nationalism--Japan--History--20th century; Natur -- Motiv; Landschaft -- Motiv; Jōmon; Archäologie; Nationalismus; Japan